2024 Inaugural OTC Hearing Aid and Hearing Self-Care Symposium: OTC Hearing Aids Regulatory Panel - Creed, Lindsay S. (Seminars in Hearing, 2025)
Over-the-counter (OTC) hearing aids became available for purchase online, in retail stores, and in pharmacies in October 2022. As trusted sources of healthcare information, audiologists and pharmacists are likely among the first to field questions about these devices. Therefore, it is essential for them to understand their proper use, identify reliable devices, and know when to refer patients for further evaluation. Understanding the regulatory criteria for OTC hearing aids is especially important. These devices must meet specific conditions for sale, which ensure their safety and effectiveness for the public. Familiarity with these regulations will ensure that audiologists and pharmacists can help patients choose devices that meet established standards, avoiding misrepresented products. Given the visibility and accessibility of OTC hearing aids in pharmacies, pharmacists can offer initial guidance, answer questions, and help patients navigate the available options on their shelves. Audiologists, experts in hearing health, can assess a patient's hearing needs and determine whether an OTC hearing aid is a suitable option, guiding the patient's device selection. This article will summarize a presentation given to audiologists and pharmacists by Julie Cohen, AuD, PhD, an audiologist and scientific reviewer at the Food and Drug Administration (FDA), on the FDA's OTC Hearing Aid Regulations. Audience questions were answered by Dr. Cohen and by FDA lead scientific reviewer, Lindsay Devries, AuD, PhD.
Keywords: OTC hearing aids; audiology; pharmacy; Food and Drug Administration; regulations